(untitled) (LIS TODAY, 2021)
The present survey was conducted to find out that how library comes handy in crucial time like shutting of internet by the Government during exam time. Library emerged as a savior for the students. During an internet shutdown, students are barely accessible to the information. Thus this survey reveals that PG students of Assam University prefer to find the resources they find through the internet more easier than the resources available in their library. The shutting down of internet during exam time does leads the students to the psychological phase and thus this phenomenon resulted in fear of failure in exam. The researcher evaluated every perspective of the present study that directly or indirectly related to the PG students of Assam University Silchar about their views on how their library and library professional helps them in internet shutdown during exam time. However, every research has a future scope.